School Organization Effective Concept in the Industrial Revolution 4.0 Era - Aditya Wijaya; Erra Sanianingtyas; Femi Setyowati; Imron Arifin; Maulana Amirul Adha (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Singaperbangsa Karawang, 2022)
The purpose of this study is to explain (1) educational opportunities and challenges in the industrial revolution era 4.0, (2) the concept of effective school organization, (3) the characteristics of effective school organization, (4) efforts to make schools effective, (5) effective leadership of school organizations in the industrial revolution era 4.0, (6) effective school organization management systems, (7) school technological innovation in the industrial revolution 4.0 era, and (8) the potential for effective schools in the future. This research uses the literature research method which is the method obtained from research by reading, researching and studying national books and articles that are relevant to the concept of effective school organization in the industrial revolution era 4.0. Based on the results of the literature study found an explanation of the challenges and education in the era of the industrial revolution 4.0, the concept of effective school organization, the characteristics of effective school organizations, the struggle to make schools effective, organizational leadership in the industrial revolution era 4.0, effective school organization management systems, school technology innovation in the era of the industrial revolution 4.0, and the potential for effective schools in the future.